IL-27, IL-30, and IL-35: A Cytokine Triumvirate in Cancer - Kourko, Olena; Seaver, Kyle; Odoardi, Natalya; Basta, Sameh; Gee, Katrina (Frontiers in Oncology, 2019)
The role of the immune system in anti-tumour immunity cannot be overstated, as it holds the potential to promote tumour eradication or prevent tumour cell escape. Cytokines are critical to influencing the immune responses and interactions with non-immune cells. Recently, the IL-12 family of cytokines has accumulated newly defined members each with specific immune functions related to various cancers and tumourigenesis. There is a need to better understand how cytokines like IL-27, IL-30 and IL-35 interact with one another, and how a developing tumour can exploit these interactions to enhance immune suppression. Current cytokine-based immunotherapies are associated with cytotoxic side effects which limits the success of treatment. In addition to this toxicity, understanding the complex interactions between immune and cancer cells may be one of the greatest challenges to developing a successful immunotherapy. In this review, we bring forth IL-27, IL-30, and IL-35, “sister cytokines”, along with more recent additions to the IL-12 family, which serve distinct purposes despite sharing structural similarities. We highlight how these cytokines function in the tumour microenvironment by examining their direct effects on cancer cells as well their indirect actions via regulatory functions of immune cells that act to either instigate or inhibit tumour progression. Understanding the context dependent immunomodulatory outcomes of these sister cytokines, as well as their regulation within the tumour microenvironment, may shed light onto novel cancer therapeutic treatments or targets.